A conceptual framework of Malaysian rice post harvest losses management best practices adoption - Mohd Norazmi Nodin,; Zainol Mustafa,; Saiful Izzuan Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Strengthening the food value chain through minimizing the losses is crucial in the post-production stage as these activities are significant in obtaining production efficiency. One of the key strategies is to adopt good agricultural practices (GAPs). The GAPs encompass combinations of principles to apply during food production processes to assure food safety, quality, and environmental sustainability. Its implementations in the food value chain involved on-farm production and post-production, including in the post-harvest losses (PHLs) activities. We develop a conceptual framework of PHLs best practices adoption based on the binary logit and probit model for Malaysia’s paddy and rice industry. This framework covers PHLs sequence activities from harvesting, transporting, drying, milling, and storing. Therefore, the appropriate policies or regulations of the GAPs compliance related to PHLs activities could be improved, where the imperative is given to minimizing the losses that occur along the PHLs value chain while obtaining production efficiency. These efforts would also help the nation to empower its food security agenda and attaining sustainability rice development.